KEPRIBADIAN KONSELOR DAN PEMBENTUKAN KARAKTER SISWA DI SEKOLAH - Hengki Yandri (Tarbawi : Jurnal Ilmu Pendidikan, 2016)
In general, the purposes of education in Indonesia is to build a character of students, but the fact tell a different version. Until now education in Indonesia still face a crisis in character. As example; found a student cheating, and lack of will to learning in school and at home, more than that we still found a criminalization, ect. A way to handle a problem of build the student character is with a modelling by personalities of counselor as educator.